Respon dan Koping Ibu Primipara Dan Nullipara yang Mengalami Histerektomi - Lismidiayati, Wiwin; Setyowati,; Afiyanti, Yati (Jurnal Keperawatan Soedirman, 2011)
Background. Hysterectomy is a surgical procedure to remove partially or totally the uterus. Objective. The aim of this research is to develop conceptual framework of responses and coping of primiparous and nulliparous mother who are experienced hysterectomy. Method. This is a qualitative study using Grounded Theory approach. Seven participants who were joined this study were gained by theoretical sampling method. Result. Result shows that the responses of primiparous and nulliparous mothers who were experienced hysterectomy were avoiding loss, bargaining, and accepting loss. Coping mechanisms that were used to deal with loss process consisted of problem-focused coping and emotional focused coping. One factors that affecting mothers’ responses and coping to deal with loss process was social support. Conclusion. This research describes things that are experienced and felt by grieving mothers because of loss process that was mainly related to mothers’ responses and coping and its influence factors to health care providers mainly nurses.